Anisotropy of acoustic emission and Portevin– Le Châtelier phenomena in polycrystalline aluminium alloys subjected to tensile tests - Pawełek, A; Kuśnierz, J.; Jasieński, Z.; Ranachowski, Zbigniew (Archives of Acoustics, 2006)
In the present work the acoustic emission (AE) method has been used in the plastic instability investigations related to the Portevin–Le Châtelier phenomenon (PL effect, nonhomogeneous strain, jerky flow) occurring in polycrystalline aluminium alloys subjected to tensile tests at ambient temperature. There have been observed very essential correlations between AE and PL phenomena and a strong anisotropy of both these effects in samples cut at various angles with respect to the initial rolling direction has been found. The results of AE measurements were obtained using a new AE analyser and, for a few samples, they have been compared with those obtained applying an analyser of older generation, used till now. Moreover, the new software allowed additionally to carry out the analysis of single AE events, which, in turn, created better possibility to determine the relations between the nonhomogeneous strain mechanisms of the PL type and the mechanisms of AE events generation. The results are discussed also in the context of the existing models of the PL effect and the theoretical concepts of AE sources.